2022
DOI: 10.3389/fcimb.2022.856711
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Porcine Epidemic Diarrhea Virus by Cinchonine via Inducing Cellular Autophagy

Abstract: Porcine epidemic diarrhea virus (PEDV) could cause lethal diarrhea and dehydration in suckling piglets, which can adversely affect the development of the global swine industry. The lack of effective therapeutical and prophylactic treatment especially for PEDV variant strains underlines the importance of effective antiviral strategies, such as identification of novel antiviral agents. In the present study, the antiviral activity of cinchonine against PEDV was investigated in Vero CCL81 and LLC-PK1 cells at a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Based on the above findings which demonstrated that CEP could significantly reduce PEDV replication in LLC-PK1 cells, we investigated the antiviral mechanism by which CEP inhibits PDCoV infection. It has been reported that rapamycin could inhibit PEDV infection in porcine intestinal epithelial cells by inducing autophagy ( Ko et al., 2017 ), and cinchonine can induce autophagy to inhibit porcine epidemic diarrhea virus ( Ren et al., 2022 ). Therefore, we hypothesized that the inhibitory effects of CEP on PDCoV infection rely on autophagy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the above findings which demonstrated that CEP could significantly reduce PEDV replication in LLC-PK1 cells, we investigated the antiviral mechanism by which CEP inhibits PDCoV infection. It has been reported that rapamycin could inhibit PEDV infection in porcine intestinal epithelial cells by inducing autophagy ( Ko et al., 2017 ), and cinchonine can induce autophagy to inhibit porcine epidemic diarrhea virus ( Ren et al., 2022 ). Therefore, we hypothesized that the inhibitory effects of CEP on PDCoV infection rely on autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagosomes fuse with lysosomes to form autophagylysosomes, which remove damaged cellular components and serve as a defense mechanism to protect the host from viral infection ( Yordy and Iwasaki, 2011 ). Studies have shown that rapamycin limits PEDV, MERS-CoV and TGEV infection by inducing autophagy ( Guo et al., 2016 ; Kindrachuk et al., 2015 ; Ko et al., 2017 ), and cinchonine-induced autophagy can inhibit PEDV infection ( Ren et al., 2022 ). These results suggest that autophagy inducers can inhibit viral infection by inducing autophagy ( Ren et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, several advances have been accomplished in developing anti-PEDV drugs, and there has been a growing interest in the use of the main components of herbal extracts as suitable alternative sources for the development of antiviral agents ( Gao et al., 2020 ). For instance, puerarin ( Zhang et al., 2021 ; Ren et al., 2022 ) has been reported to inhibit PEDV replication and pro-inflammatory response, alleviating intestinal injury and modulating intestinal microorganisms in PEDV-challenged piglets ( Wu et al., 2020 ; Wu et al., 2021 ), while glycyrrhizin has been noted to inhibit PEDV infection and decrease pro-inflammatory cytokine secretion via the HMGB1/TLR4-mitogen-activated protein kinase (MAPK) p38 pathway ( Gao et al., 2020 ). Furthermore, monolaurin has been observed to exert a protective effect against PEDV infection in piglets by regulating the interferon pathway ( Zhang et al., 2021 ); cinchonine has been found to suppress PEDV infection by inducing autophagy in the early stage of PEDV replication ( Ren et al., 2022 ); and ergosterol peroxide has been reported to restrain multiple stages of the PEDV life cycle by suppressing ROS generation and the p53 signaling pathway ( Liu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, puerarin (Zhang et al, 2021;Ren et al, 2022) has been reported to inhibit PEDV replication and pro-inflammatory response, alleviating intestinal injury and modulating intestinal microorganisms in PEDVchallenged piglets (Wu et al, 2020;Wu et al, 2021), while glycyrrhizin has been noted to inhibit PEDV infection and decrease pro-inflammatory cytokine secretion via the HMGB1/ TLR4-mitogen-activated protein kinase (MAPK) p38 pathway (Gao et al, 2020). Furthermore, monolaurin has been observed to exert a protective effect against PEDV infection in piglets by regulating the interferon pathway (Zhang et al, 2021); cinchonine has been found to suppress PEDV infection by inducing autophagy in the early stage of PEDV replication (Ren et al, 2022); and ergosterol peroxide has been reported to restrain multiple stages of the PEDV life cycle by suppressing ROS generation and the p53 signaling pathway (Liu et al, 2022). Although quercetin 7rhamnoside did not directly interact with or inactivate PEDV particles, it affected the initial stage of PEDV infection by disturbing PEDV replication (Choi et al, 2009).…”
mentioning
confidence: 99%